Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979189
|View full text |Cite
|
Sign up to set email alerts
|

Publics in practice

Abstract: Today, commodity technologies like mobile phones-once symbols of status and wealth-have become deeply woven into social and economic participation in Western society. Despite the pervasiveness of these technologies, there remain groups who may not have extensive access to them but who are nonetheless deeply affected by their presence in everyday life. In light of this, we designed, built, and deployed a ubiquitous computing system for one such overlooked group: the staff and residents at a shelter for homeless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(18 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Examples include giving voicemail to homeless individuals in the US [9]; offering ad-hoc group support for NGOs [27]; delivering health information [36]; bringing web content to resource-constrained classroom settings [13]; and exchanging agricultural advice for [32] and by [29] farmers in India.…”
Section: Related Workmentioning
confidence: 99%
“…Examples include giving voicemail to homeless individuals in the US [9]; offering ad-hoc group support for NGOs [27]; delivering health information [36]; bringing web content to resource-constrained classroom settings [13]; and exchanging agricultural advice for [32] and by [29] farmers in India.…”
Section: Related Workmentioning
confidence: 99%
“…Le Dantec (2016) also situates technological design interventions towards vulnerable communities, in this case around homelessness, and the relationship between the service providers and their clients (Le Dantec 2012), towards understanding the gulf between what is required for technological adoption, a process far beyond the provision of technological access (Le Dantec et al 2011). Major events also often bring communities together, highlighting the need for cooperation and communication between different the stakeholders within them.…”
Section: Technological Interventions For Community Participation and mentioning
confidence: 99%
“…To cater specifically to the need of communication between shelter staff and the homeless regarding available services, reminders about appointments, preservation of any accumulated knowledge and experiences of homelessness, and any inquires beneficiaries may have, Le Dantec et al [8] created the Community Resource Messenger-Web Application (CRM). They found that it enabled "immediate action to be taken" [8] regarding any issues that arose via the application and amplified the relationships between staff and residents. In this sense, mobile and information technologies assist in connecting the homeless population with friends and family [8], and are also an important factor in building collaboration in neighbourhoods [26].…”
Section: Background and Related Workmentioning
confidence: 99%
“…They found that it enabled "immediate action to be taken" [8] regarding any issues that arose via the application and amplified the relationships between staff and residents. In this sense, mobile and information technologies assist in connecting the homeless population with friends and family [8], and are also an important factor in building collaboration in neighbourhoods [26]. Ultimately, it is these social networks and ties that have an impact in whether or not the person is able to get off the street [7].…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation